The Indirect Expropriation Clause Clarified in Recent Colombian BITs: A ‘new lease of life’ for the preservation of the host State’s regulatory space? - Dorce, Milcar Jeff (Latin American Journal of Trade Policy, 2023)
Over the past two decades, Caribbean states have been faced with a significant number of investment arbitration proceedings in which investors have claimed that public interest regulatory measures constitute indirect expropriations of foreign investment. As a result, arbitral tribunals have ordered host states to pay heavy compensation to foreign investors. To preserve its right to regulate in the public interest, Colombia has clarified the indirect expropriation clause in most of its recent international investment agreements, clarifying the extent to which a public interest regulation that affects foreign investment constitutes an indirect expropriation. This article seeks to determine to what extent the new clauses of the Colombian agreements contribute to preserving the state’s right to regulate in the public interest.